Analisis Pengaruh Efektivitas Iklan, Word Of Mouth, Citra Merek Terhadap Keputusan Pembelian Mrprabspomade - Pringgondani Pringgondani (Universitas Batanghari Jambi, 2022)
The from physical to digital forms requires companies to develop their marketing. The purpose of this research is to know how the influence of advertising effectiveness, word of mouth, and brand image to the purchasing decision Mrprabspomade. The sampling in this study was convenience sampling and the sample that can be used in this research is 100 datas (round figures using Slovin (99,9). And the methods for the data analysis is regression, which are simple regression and multiple regression. The results of this study are positive influence on the effectiveness of advertising purchasing decisions. With the t value of 9.698 or more than t table 1.9845. Word of mouth has positive influence on purchasing decisions, with the t value of 9.192 or more than t table 1.9845. Brand image has positive influence on purchasing decisions, with the t value of 8.842 or more than t table 1.9845. Simultaneous with the test, all the independent variables (effectiveness of advertising, word of mouth and brand image) significant influence on purchasing decisions, the calculated F value of 54.923 over the F table at 2.70 and with a significant level of 0.000 <0.05, it can be concluded that the H04 is rejected and Ha4 accepted.